Evaluation of Cardiopulmonary Complication Rates after Port Insertion: Is a Postoperative X-Ray Needed?. Issue 7 (July 2017) - Vaughan, Justin G.; Cauthen, Allison B.; Allen, Ahkeel; Dale, Paul
It is customary for a postoperative chest radiograph to be obtained after fluoroscopic guided port insertion to exclude acute complications. In this review, we provide a cost-benefit analysis by examination of acute postoperative complications detected by postoperative port insertion chest films at our institution. We conducted a retrospective chart review of complications associated with port insertion procedures performed over a 5-year period. Our study included only ultrasound-assisted internal jugular venous or landmark guided subclavian ports placed with the assistance of fluoroscopy. A total of 519 port insertions were reviewed and there was noted to be a postoperative complication rate of 0.58 per cent. The operative note for each complication described a procedural abnormality that suggested a chest film would be of medical benefit. The total price of postoperative chest radiographs was $179, 400. Performing chest X-ray films on asymptomatic patients after fluoroscopic guided placement of ports proved to be of no medical advantage to 516 out of 519 patients. Given the extremely low complication rate and financial burden placed on the patient population, we propose discontinuing routine use of postoperative port placement chest radiographs as a way to alleviate unwarranted medical cost.